Pressure dependence of electron- and hole-consuming reactions in photocatalytic water splitting on Pt/TiO2 studied by time-resolved IR absorption spectroscopy - Akira Yamakata; Taka-aki Ishibashi; Hiroshi Onishi (International Journal of Photoenergy)
The decay kinetics of photogenerated electrons in the water splitting reaction on a Pt/TiO2 photocatalyst was studied by time-resolved IR absorption spectroscopy. The decay of the photogenerated electrons within 2 μs was decelerated when the catalyst was exposed to water vapor. The holes were consumed by the reaction with water instead of by the recombination with the electrons. On the other hand, the decay at 10–900 μs was accelerated by the exposure. The electrons were consumed by the reaction with water. The rate of the hole-consuming reaction was independent of the pressure of water vapor, whereas that of the electron-consuming reaction increased with the pressure from 1 to 10 Torr. The different pressure dependences indicate different reactants involved in the oxidative and reductive reactants.